THE QUIT INDIA MOVEMENT: REVOLUTIONARY SPIRIT OF A NATION - Monika Rani (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Quit India Movement marked an important phase in the Indian freedom struggle. After years of struggle against the Raj, Mahatma Gandhi ji launched a nationwide movement for the freedom of India. Through this movement, Gandhi ji united millions of Indian people from diverse socio-economic backgrounds for a common purpose. This article will explore the ethos, revolutionary spirit, and impact of the movement on Indian people. The British government repressed this movement mercilessly and adopted every available measure to suppress the revolutionary spirit of the people. However, Indian masses reiterated their demands and fought valiantly against the oppression. This study will analyze the revolutionary spirit of the people and the legacy of the movement.